Hannah Curran. History of the Civil Rights Movement - Curran , Hannah (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. Fannie Lou Hamer was a civil rights leader, promoting voting rights for African Americans. She additionally was heavily involved in promoting the need for women’s rights. Her involvements include working with the Student Non Violence Committee as well as being a founder of the Mississippi Freedom Democractic Party.